Contribution to Agility, Endurance, and Leg Length Towards The Ability Dribbling and Passing in Futsal Extracurricular Religion at SMK Negeri 3 Semarang (Journal of Physical Education and Sports, 2019)
The technique that must be mastered by each player is to pass (passing), herding (dribbling), kicking (shooting), controlling, heading, a futsal player must also pay attention to physical supporting factors that can support good mastery of technique is speed, muscle strength, endurance, flexibility, accuracy, explosive power, coordination reaction, balance and agility. How big is the contribution between agility, endurance, leg length to dribbling ability and passing? This type of research is a type of research with a quantitative approach emphasizing its analysis on numerical data (numbers) processed by statistical methods. Inferential research analyzes the relationship between variables by testing hypotheses. The sample in this study was taken from 50 people who practiced at SMKN 3 Semarang. The number of samples is 50 people because there are only 50 people who practice gymnastics at SMKN 3 Semarang. The sampling technique in this study was the purposive sampling method. The results of the study were obtained from tests of passing ability and dribble ability conducted to 50 students who participated in futsal extracurricular activities at SMKN 3 Semarang. Agility will be able to improve the passing ability of students who take futsal extracurricular activities at SMKN 3 Semarang at 7.7%. Durability will be able to increase the passing ability of students who take futsal extracurricular activities at SMKN 3 Semarang at 34.9%. The leg length will be able to increase the passing ability of students who take futsal extracurricular activities at Vocational High School 3 Semarang at 32.4%. Agility will be able to increase the dribble ability of students who take futsal extracurricular activities at SMKN 3 Semarang by 29.5%. The length of the limbs will be able to increase the dribble ability of students who take futsal extracurricular activities at SMKN 3 Semarang at 12.8%.